Antimicrobial resistances of escherichia coli isolated from buteo rufinus - Mehmet Fatih Birdane; Zeki Aras; Gökçenur Sanioğlu Gölen; Mehmet Volkan Yaprakci; Hasan Hüseyin Hadimli (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to determine microbiological examination of cloacal swab specimens taken from Long-legged Buzzards (Buteo rufinus) and antibiotic resistance of isolated Escherichia coli (E. coli) strains. Materials and Methods: The cloacal swab specimens were obtained from 24 Long-legged Buzzards which were admitted to Afyon Kocatepe University Veterinary Faculty clinics. The samples were cultured on different media for various bacteria (Salmonella species, E. coli, Mycoplasma, Gram-positive cocci, etc.). The media were incubated at 37°C in aerobic and microaerophilic conditions. ISO 6579 protocol was applied for Salmonella. In addition, antibiotic susceptibilities of the isolated bacteria were determined. Results: Twenty-four E. coli were isolated from all cloacal swab samples. In addition, Enterococcus faecalis was isolated from one sample. While all E. coli isolates were susceptible to florfenicol and ciprofloxacin, other antibiotics were found to be susceptible at different rates. Conclusion: This study is important because it is the first microbiological examination of cloacal swaps of Long-legged Buzzards in this Country. In addition, it was significantly evaluated that E. coli strains were resistant to various antibiotics with different ratios while no antibiotics are used using antibiotics in Long-legged Buzzards.